Implementasi Instrumen Assessment for Learning pada Pembelajaran Berbasis Proyek untuk Meningkatkan Level Kemampuan Berpikir Kritis - Oktaviyanti, Fadhilah; Viyanti, Viyanti (EduFisika: Jurnal Pendidikan Fisika, 2025)
The purpose of this research is to determine whether the Assessment for Learning instrument in project-based learning can enhance students' critical thinking skills and to describe each level of critical thinking skills achieved by students influenced by Assessment for Learning in project-based learning.  The quantitative sample in this study is the X.1 grade students at State Islamic High School 1 Central Lampung for the 2024/2045 academic year, even semester.  Meanwhile, the qualitative sample used consists of one student from each measurable of critical thinking skill.  This study uses a mixed-method research approach with an Explanatory Sequential Design.  The research results show that after the use of the AfL instrument in project-based physics learning, students' critical thinking skills improved.  This is evident from the results of the average pretest and posttest score difference test using the Paired Sample T-Test, which showed a significance value of < 0.05.  The improvement in critical thinking skills is supported by the calculation of N-Gain, which falls within the moderate criteria